(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The Taguibo Watershed is a key biodiversity area in Caraga Region, providing a source of water to the entire city of Butuan. A gender-based analysis of Indigenous Peoples (IPs) in Taguibo watershed aims to determine the socioeconomic, conservation, environmental management practices and perception of male and female respondents. Following a mixed-method approach, the data were gathered through the use of structured survey questionnaires, key informant interviews, and validation through a focus group discussion. Data were analyzed using Spearman Correlation to determine the relationship. A total of 323 IP respondents, 113 (35%) were male and 210 (65%) were female. Most had low education and family income, high percentage of the occupation were housewives and farmers. Gender had a very highly significant (p.<0001) relationship on occupation, but household members (p 0.4460), educational attainment (p 0.0335), and family income (p 0.1299) have no significant relationship. The study reveals that gender should not be a basis for determining one’s ability to participate in the conservation and effective management of the Taguibo Watershed. Respondents expressed confidence that continued direct management and conservation of the watershed by members of the indigenous cultural community can lead to sustainable outcomes.